Crystallographic identification of an ordered C-terminal domain and a second nucleotide-binding site in RecA: new insights into allostery - Krishna, R. (Oxford University Press, 2006)
RecA protein is a crucial and central component of the homologous recombination and DNA repair machinery. Despite numerous studies on the protein, several issues concerning its action, including the allosteric regulation mechanism have remained unclear. Here we report, for the first time, a crystal structure of a complex of Mycobacterium smegmatis RecA (MsRecA) with dATP, which exhibits a fully ordered C-terminal domain, with a second dATP molecule bound to it. ATP binding is an essential step for all activities of RecA, since it triggers the formation of active nucleoprotein filaments. In the crystal filament, dATP at the first site communicates with a dATP of the second site of an adjacent subunit, through conserved residues, suggesting a new route for allosteric regulation. In addition, subtle but definite changes observed in the orientation of the nucleotide at the first site and in the positions of the segment preceding loop L2 as well as in the segment 102–105 situated between the 2 nt, all appear to be concerted and suggestive of a biological role for the second bound nucleotide.